Preoperative prediction of early recurrence of HBV-related hepatocellular carcinoma (≤5 cm) by visceral adipose tissue index - Wu, Zong-qian; Cheng, Jie; Xiao, Xi-xi; Zhang, Hua-rong; Wang, Jian; Peng, Juan; Liu, Chen; Cai, Ping; Li, Xiao-ming (Frontiers in Surgery, 2023)
Background This study aimed to investigate whether visceral adipose tissue index (VATI) is a significant risk factor for the early recurrence (ER) of HBV-related hepatocellular carcinoma (HCC) (≤5 cm) after hepatectomy. Methods The recruited cohort patients who were positive for hepatitis B virus, presented with surgically confirmed HCC (≤5 cm) from Army Medical University (internal training cohort: n = 192) and Chongqing Medical University (external validation group: n = 46). We measured VATI, subcutaneous adipose tissue index (SATI) via computed tomography (CT). ER was defined as recurrence within 2 years after hepatectomy. The impact of parameters on outcome after hepatectomy for HCC was analyzed. Results Univariate analysis showed that alpha-fetoprotein levels (p = 0.044), body mass index (BMI) (p < 0.001), SATI (p < 0.001), and VATI (p < 0.001) were significantly different between ER and non-ER groups in internal training cohort. Multivariate analysis identified VATI as an independent risk factor for ER (odds ratio = 1.07, 95% confidence interval: 1.047–1.094, p < 0.001), with a AUC of 0.802, based on the cut-off value of VATI, which was divided into high risk (≥37.45 cm2/m2) and low risk (<37.45 cm2/m2) groups. The prognosis of low risk group was significantly higher than that of high risk group (p < 0.001). The AUC value of VATI in external validation group was 0.854. Conclusion VATI was an independent risk factor for the ER, and higher VATI was closely related to poor outcomes after hepatectomy for HBV-related HCC (≤5 cm).